Analysis of Health Education Using Video Media on Pregnant Women's Knowledge of Chronic Energy Deficiency in the Kenarilang Health Center Work Area, Alor Regency - Metriana Eli (Universitas STRADA Indonesia, 2025)
Based on Riskesdas data in 2018, the prevalence of chronic energy deficiency cases in Indonesia in pregnant women was 17.3%. Then in the province of East Nusa Tenggara, the prevalence was 36.8%. While in Alor district, the prevalence was 41.15%. Data from the Kenaril Health Center in September 2023 showed that 23 pregnant women experienced chronic energy deficiency. Meanwhile, a preliminary study in the Kenaril Health Center Work Area also showed a lack of knowledge of pregnant women about Chronic Energy Deficiency. The purpose of the study was to analyze Influence Education Health Using Video Media Against Knowledge Mother Pregnant About Lack Energy Chronicle. This research design is one group pre test post test . The sample is some pregnant women in the Kenarilang Health Center Working Area, Alor Regency, as many as 30 people. Respondents were taken with technique accidental sampling . Analysis using the Wilcoxon Test. Most of the mothers' knowledge before health education was in the poor category as much as 56.7%. Most of the mothers' knowledge after education was in the good category as much as 70%. The Effect of Health Education Using Video Media on Pregnant Women's Knowledge About Chronic Energy Deficiency in the Kenarilang Health Center Work Area, Alor Regency in 2024 with a p-value of 0.000. Health education has been shown to increase mothers' knowledge about Chronic Energy Deficiency, so it is hoped that the risk of chronic energy deficiency in the Kenarilang Health Center Work area, Alor Regency can be reduced.